The last list of Miss Judith Kratt : a novel - Bobotis, Andrea (Sourcebooks Landmark, 2019)
"Judith Kratt inherited all the Kratt family had to offer - the pie safe, the copper clock, the murder that no one talks about - and she knows in her old bones that it's time to make an inventory of her household and its valuables. But she finds that cataloging the family heirlooms can't contain their misfortunes, not when her wayward sister suddenly returns, determined to expose secrets that the Kratts had hoped to take to their grave. Interweaving the present with chilling flashbacks from one fateful evening in 1929, Judith pieces together the influence of her family on their small South Carolina cotton town, learning that the effects of dark family secrets can last for decades." --